2005
DOI: 10.1111/j.1743-5013.2005.20415.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary Headache Disorders and Circadian Biology: A Clinical, Imaging, and Therapy Perspective

Abstract: Primary headache syndromes such as hypnic headache, and trigeminal autonomic cephalgias (TACs) such as cluster headache, paroxysmal hemicrania, and SUNCT (Short-lasting Unilateral Neuralgiform headache attacks with Conjunctival injection and Tearing), are associated with varying degrees with attacks that occur with circadian rhythmicity. In hypnic headache, the attacks occur exclusively during sleep, and in cluster headache the attacks predominate in sleep in 75% of patients. The TACs, especially cluster heada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 89 publications
(157 reference statements)
0
11
0
Order By: Relevance
“…Attacks usually occur about 90 minutes after the patient falls asleep, which coincides with the first REM sleep, 11 although this is less apparent in chronic CH 12 . It has been observed that cluster periods may be triggered by traveling through different time zones, which may reflect hypothalamic activity and diurnal variation in CH 13 …”
Section: Cluster Headachementioning
confidence: 99%
See 3 more Smart Citations
“…Attacks usually occur about 90 minutes after the patient falls asleep, which coincides with the first REM sleep, 11 although this is less apparent in chronic CH 12 . It has been observed that cluster periods may be triggered by traveling through different time zones, which may reflect hypothalamic activity and diurnal variation in CH 13 …”
Section: Cluster Headachementioning
confidence: 99%
“…The apparent discrepancies between the TACs may be reflected in their responses to medications; for instance oxygen an acute abortive therapy in CH may possibly act either on abnormal mitochondrial energy metabolism 132 or in nocturnal CH attacks, which are possibly due to hypoxia in an already physiologically compromised hypothalamus 13,92,93 . The lack of response to oxygen in PH and SUNCT may be because the attacks are too short for an abortive to have a meaningful effect, or because the pathophysiology of these syndromes is different.…”
Section: The Future For Treatment Of Tacsmentioning
confidence: 99%
See 2 more Smart Citations
“…Migraine has also been linked to somnambulism, which occurs during non‐REM stage of sleep 4 . A preponderance of migraine in the morning hours 5 has been used as an argument for a pivotal role of melatonin and the circadian clock‐system in migraine pathophysiology 6 . If this is true, studies of the circadian pattern of migraine are essential to shed light on the postulated “migraine generator.” 7 However, the prevalence of chronic morning headache was 7.6% in a general population, 8 and the morning preponderance has been questioned 9,10 .…”
mentioning
confidence: 99%